Prevalence of Musculoskeletal Symptoms in Obesity - Dr. Aishwarya Kanhere (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background and aim Overweight and obesity are increasing in India. Obesity is nowadays the most common metabolic disease in the world. According to WHO, epidemic size posing a key health problem in developed and developing countries. In epidemiological studies, it is clear that more body weight that affects all diseases of the musculoskeletal system, such as osteoarthritis, metabolic diseases, such as osteoporosis, gout, connective tissue diseases – rheumatoid arthritis, systemic lupus erythematosus, rare diseases like idiopathic hyperostosis, or rarely diagnosed as fibromyalgia. This study was designed to identify the prevalence of musculoskeletal symptoms in individuals with obesity. Methodology Cross-sectional study with simple random sampling. Both the genders male and female involved with sample size 100. Demographic information and clinical evaluation was obtained from questionnaire. Results were obtained on the basis of graphs and analysis of the data was done. Results and conclusion Total, 100 subjects were assessed, of which 56 were female and 44 were male. Mean age of the subjects was 38 years and mean body-mass index was 33.88 kg/m2. All subjects had musculoskeletal pain in at least one anatomical region. Anatomical regions by pain affected were the knees, lower back and ankles and feet, wrist/hands/fingers. In conclusion, showed that there is a high prevalence of musculoskeletal in obese people.